RISK FACTORS ASSOCIATED WITH NEURODEVELOPMENTAL DISORDERS IN HIGH SOCIOECONOMIC STATUS FAMILIES: BRIEF INDIAN ANALYSIS - GOPALKRISHNAN, IYER KAMLAM; VENKATESAN, S. (Innovare Journal of Education, 2020)
This study seeks to identify parental prenatal, perinatal and postnatal risk factors of Neurodevelopmental Disorders (NDD) in comparison to Typically Developing (TD) children, all from high Socioeconomic Status (SES) families. A unified definition of NDD in terms of delays in development was employed for the purpose of this study. SES was understood as an important variable in the context of NDD. We employed a cross-sectional/comparative two-group survey design. It included parents of 60 children: 32 children with NDD and 28 children with TD. The developmental assessment was conducted for all the children for their classification into NDD and TD groups. Results depicted significant differences in the family history of mental illness or NDD, perinatal factors rather than prenatal and postnatal factors. On measures of association and variance, composite perinatal factors were observed to have a small effect on NDD, while the pre and postnatal showed a negligible impact. The interpretation and its application for improving the prevalence of NDD in high SES families in an Indian urban set-up were discussed.